Staging modernist lives : H.D., Mina Loy, Nancy Cunard, three plays and criticism - Colby, Sasha, 1978- (McGill-Queen's University Press, 2017)
"The first objective of Staging Modernist Lives is to illuminate the work and lives of three important but somewhat underrepresented modernist writers: H.D. (Hilda Doolittle, 1886-1961), Mina Loy (1882-1966) and Nancy Cunard (1896-1965). The second is to demonstrate the ways in which these women constructed aesthetic, political, and social identities and performed these versions of themselves in their autobiographical literary work in ways that had a profound effect on the scope and course of literary modernism . The third objective is to advance a new approach in literary studies by bringing together critical theory and original play-scripts in order to analyze performed literary identity and also enact it through original, annotated, full-length performance scripts drawn from these women's autobiographical writing. As a result, the completed manuscript is a work of research-creation consisting of: (1) a critical introduction which surveys how other disciplines have adopted performative inquiry, considersexisting examples and prototypes in literary studies, and advances a methodological framework for a broader performative model in modernist literary studies, (2) three critical prefaces which argue how dramatization deepens our research understanding in the case of each writer, (3) three original, full-length, annotated play-scripts: The Tree (H.D.), The Mina Loy Interviews (Loy) and These were the Hours (Cunard). The intent is to advance a theoretical and practice-based model which enhances scholarly understanding and provides suggestive avenues for scholars seeking to reach broader and more diverse audiences."--